Patient safety culture attitudes among different healthcare professionals in selected general and district hospitals: a preliminary study - Wan Zulkipli, Nuaim; Taib, Ibrahim Adham; Samsuddin, Niza; Md Isa, Muhammad Lokman (Human factors and Ergonomics Society Malaysia, 2018)
According to the World Health Organization, the reduction of accidental injury during medical procedure is heavily influenced by patient safety culture in hospitals. Patient safety culture is a collective shared behavior ranging from individual and group values, attitudes and perception that determine the commitment of an organization‟s safety management. Organizations such as the National Health Services and the National Quality Forum have suggested that by measuring patient safety culture, the healthcare industry can be improved by assessing their ability to deal with risky healthcare delivery. Because of that, a number of hospitals in developed countries such as the United Kingdom and United States of America have measured their healthcare professionals‟ patient safety attitude by using various validated safety attitude tools. One of the most commonly used tools is the Safety Attitude Questionnaire (SAQ), which has been proven by many studies to have good construct validity, internal consistency and domains properties that are associated with patient safety outcomes. The SAQ can measure healthcare professionals‟ attitude through six domains, which are teamwork climate, safety climate, perception on management, job satisfaction, working condition and stress management. Despite its importance, there is insufficient data on patient safety culture among Malaysian healthcare professionals. Thus, this study was designed to investigate differences in patient safety culture attitudes among selected healthcare professionals and types of hospital. The data analyses include descriptive, one-way ANOVA test and independent t-test in SPSS. The findings showed that doctors, nurses, pharmacists and medical assistants responded differently for safety climate, job satisfaction and working condition while teamwork climate, perception on management and stress recognition are not significantly different. The results also showed that there are significant differences between the general and district hospitals for safety climate in all domains except for working conditions. These results indicate that healthcare profession and type of hospital were factors for the SAQ scores.